Effect 10-Weeks Extracurricular Sports Training Program in Physical Education Courses for Male Students of University of Medicine and Pharmacy - Thi, Tu Tran; Ngoc, Cuong Do (International Journal of Membrane Science and Technology, 2023)
Backgrounds: Extracurricular sports in schools is an activity with a very important position and great meaning to help students improve the quality of the subject of physical education, meet training needs of students. Purposes: The purpose of this study is to evaluate the impactiveness of the extracurricular sports training program (ESTP) on the physical development of male students at University of Medicine and Pharmacy after in 10 weeks of experiment. Methods: A total of 60 healthy male students were randomly selected and divided into 2 groups: an experimental group of 30 students and a control group of 30 students. In the study, used 5 criteria to evaluate the physical development, such as 30-s sit-up test, 30-m sprint test, 4 × 10-m shuttle run test, standing long jump test, and 5-min running field test. Results: After 10 weeks of applying for the ESTP, the experimental group had a higher rate of physical growth than the control group in all 5 tests. Accordingly, 30-s sit-up test increased the highest by 27.72%, 30-m sprint test increased by 17.52%, standing long jump test increased by 16.26%, 5-min running test increased by 16.69%, 4 × 10-m shuttle run test increased by 6.53%. Conclusions: The ESTP has many improvements and benefits than the current program. It creates a diverse and healthy learning and physical training environment and meets the learning needs of students at the University of Medicine and Pharmacy. We recommend actively using this program in the coming time to improve the quality of physical education.